GEOECONOMIC ASPECT AND PROCESSES BEFORE THE GLOBAL SPATIAL DEVELOPMENT OF THE MODERN WORLD - Petrov, Kamen (Global Prosperity, 2021)
The article examines the main issues related to the development of the geoeconomy in the context of globalization and regional development. The mysteries of geoeconomics from the point of view of spatial development are being clarified. First, the author pointed out certain aspects of spatial development and the definition of the main approaches for clarifying the subject of geoeconomics, clarified the differences in the interpretation of the main problems related to the implementation of regional policy in the nation-state. Second, the author derived the models for determining the spatial development and the nature-man-economy relation from the point of view of the institutional development and the economic activity in the conditions of the dynamics of the world economy and post-Covid-19 world. Finally, the author proposed a methodical approach for the derivation of global processes with a geoeconomic sign.